The Relationship Between Self-Efficacy and Medication Adherence in Hypertension Patient - Fransiska Haryati; Puput Rosie Angraini; Titi Permaini; Rodiyanah Rodiyanah (GLOBAL HEALTH SCIENCE GROUP, 2025)
Hypertension is a state of blood pressure above normal that has an impact on increasing morbidity and mortality rates. Hypertension generally makes sufferers have a low life expectancy and still choose to coexist with hypertension. In increasing life expectancy, hypertensive patients need high self-efficacy . A patient with high self-efficacy had twice the chance of showing better adherence to treatment when compared to patients with low self-efficacy. Objective to find out the relationship between self-efficacy and adherence to treatment for hypertension. This study is included in an observational analytical study with a cross sectional design approach. The subjects of this study were selected using a random sampling technique using 90 subjects who suffered from hypertension. The method used to measure self-efficacy was using the Medication Adherence Self-Efficacy Scale-Revision (MASES-R) and measuring medication adherence was using the Morisky Medication Adherence Scale -8 (MMAS-8). The validity test results showed that 8 questions were valid (r = 0.300), while the reliability test indicated that the MASES-R questionnaire (r = 0.990) and the MMAS-8 questionnaire (r = 0.674) were considered reliable. The results showed that there was a relationship between self-efficacy and treatment compliance in hypertensive patients at the Bambu Apus Health Center where P-Value = 0.01 = < (0.05) with a contingency coefficient value of 0.638 meaning that the strength between variables at a very strong level with the direction of a positive relationship. There is a relationship between self-efficacy and adherence to treatment for hypertension (P-Value < 0.05).